Queering the matrix? language and identity troubles in HIV/AIDS contexts - Milani, Tommaso M. (Stellenbosch Papers in Linguistics Plus, 2012)
The aim of the present paper is to take a queer approach to language and HIV/AIDS discourse, one which problematizes the notions of sexual identity and group categories, and instead calls for a foregrounding of (sexual) practices and desires. In support of this argument, I will examine two very different examples of patient-doctor interaction. One is a fictional verbal exchange taken from the TV miniseries Angels in America, in which one of the main characters, the lawyer Roy Cohn, is diagnosed with HIV/AIDS. The other one is a personal experience in a state-financed medical practice in Stockholm, Sweden, where the symptoms of tonsillitis became re-interpreted by the doctor as manifestations of HIV/AIDS infection as soon as I disclosed that I was dating a man.